PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, DAN PERILAKU BELAJAR PADA TINGKAT PEMAHAMAN AKUNTANSI - Wardani, Ni Wayan Resna; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2017)
The level of understanding of accounting to be very important. Through the level of understanding of accounting can be known how adequate accounting knowledge already possessed an accountant in order to carry out the role of the accounting profession in the business world. Factors that may affect the level of understanding of accounting is a factor of emotional intelligence, intellectual, and behavioral learning. This study aimed to get empirical evidence about the influence of emotional intelligence, intellectual, and behavioral learning on the level of understanding of accounting. This research was conducted at the Faculty of Economics and Business, University of Udayana survey method using a questionnaire. Samples in this study of 160 respondents with a technical determination of the sample used is purposive sampling. Data analysis technique used is multiple linear regression. The study found that emotional intelligence, intellectual, and behavioral learning positive effect on the level of understanding of accounting. The higher the emotional intelligence, intellectual, and behavioral learning, the higher the level of understanding of accounting.
Keywords: Emotional Intelligence, Intellectual Intelligence, Behavioral Learning, Comprehension Level Accounting